Factor V Leiden Mutation in Iraqi Patients with Deep Venous Thrombosis. - Al-Allawi, Nasir; Jubrael, Jaladet MS; Hilmi, Ferial A. (Journal of the Faculty of Medicine Baghdad, 2011)
Background: Factor V Leiden is considered the most common inherited risk factor for venous thrombosis in Caucasian populations, including those in the Eastern Mediterranean region. While several studies have addressed Factor V Leiden prevalence in patients with venous thrombosis in the Eastern Mediterranean countries, none have been reported from Iraq. Objective: To study the prevalence of Factor V Leiden in an unselected group of Iraqi patients with Deep Venous thrombosis. Materials and Methods: A total of 50 unselected patients with deep venous thrombosis referred to the Medical City Teaching Hospital in Baghdad, Iraq, as well as 40 age and sex matched controls, were enrolled. The evaluation included in addition to detailed history, Factor V Leiden by polymerase Chain reaction and reverse hybridization. Results: Factor V Leiden mutation was documented in 8 patients (16%), compared to 1 control (2.5%) (Odds Ratio 7.4; p= 0.0397). The mutation was more frequent among younger patients, those with family history of thrombosis and those with recurrent thrombosis, but only the latter was of significance. Conclusions: The study suggests that Factor V Leiden is frequently encountered in Iraqi patients with Deep venous thrombosis from Baghdad, but less so than in some surrounding Eastern Mediterranean countries. Although further larger studies maybe warranted, the current study favors screening for Factor V Leiden in the workup of newly diagnosed venous thrombosis cases in this city.